Occurrence of inherited supra-subduction zone mantle in the oceanic lithosphere as inferred from mantle xenoliths from Dragon Seamount (southern Tore–Madeira Rise) - Renaud Merle; Mary-Alix Kaczmarek; Elodie Tronche; Jacques Girardeau (2016)
Spinel-bearing peridotite and pyroxenite xenoliths dredged from the Dragon Seamount (southern Tore–Madeira Rise, West Iberia and Morocco margin) give an insight into the composition of the underlying lithosphere. These xenoliths are devoid of evidence of strong host lava–peridotite interaction and re-equilibration or late impregnation in the plagioclase facies. The spinels and pyroxenes from the Dragon peridotites have compositions distinct from those of both lherzolites and harzburgites from the Iberia margin and the Mid-Atlantic Ridge. They display a highly depleted composition, in particular, high Cr-number, up to 0.63 in the spinels, consistent with a melting degree between 12 and 19%. Because of the strong chemical similarities between the Tore–Madeira Rise, Newfoundland peridotites, and peridotites from supra-subduction zones, we propose that the Dragon peridotites formed in a similar context. The pyroxenites display a cumulate texture and are probably a high-temperature–high-pressure cumulate formed by fractional crystallization from a melt. The Tore–Madeira Rise peridotites may represent a former mantle wedge in an oceanic arc, later included into the continental lithosphere and finally tectonically disseminated within the lithosphere during the rifting of the Newfoundland–Iberia continental lithosphere. As a consequence, rifting processes may produce heterogeneities in the oceanic lithosphere and influence isotopic compositions of ocean island basalt-type lavas during plume–lithosphere interactions, as inferred for the southern Tore–Madeira Rise.